Utilization of the white-rot fungus, Trametes menziesii for landfill leachate treatment - Wan Razarinah, W.A.R.; Noor Zalina, M.; Noorlidah Abdullah, (Universiti Kebangsaan Malaysia, 2015)
The study monitored the characteristics of the leachate collected from ten different landfills and presented the experimental work for the treatment of leachate by immobilized Trametes menziesii. Variation in biological oxygen demand (BOD), chemical oxygen demand (COD) and ammoniacal nitrogen (NH3-N) showed that the age of the leachate has a significant effect on its characteristics and composition. The BOD5/COD ratio tends to decrease as the age of leachate increases, varying from 0.71 for a relatively ‘fresh’ leachate to 0.62 for an older (more stabilized) one. Variations in the characteristics of the leachate suggested that these leachates are difficult to treat. The principal pollutants in the leachate samples were organic and ammonia loads. Treatment of leachate using immobilized Trametes menziesii achieved 89.14 and 2.11% removals for leachate BOD5 and COD, respectively. These findings suggested that using immobilized Trametes menziesii can remove promising percentage of BOD and COD leachate.